Retas no Espaço Projetivo de dimensão 3 - (:unkn) unknown (Universidade Federal do Amazonas, 2017)
We present in this work a study of lines in the P3, initially approached some concepts fundamental to the Algebraic Geometry, such as the projective space, projective varieties, dimension, degree and blowup. Next we study the set of the lines in the projective spaces and, more detailed, in the space P3. In which it is shown that they form an algebraic variety called the Grassman variety. We also studied the Schubert cycles and the Grassmannian Chow rings. These results apply to the study of lines on quadratic surfaces in P3. For example, it is shown that 4 lines in the general position on P3 have 2 secant lines, and that a quadratic surfaces swollen at 1 point is isomorphic to the plane swollen at 2 points.
Keywords: Retas no espaço; Superfícies quadráticas; Variedades Grassmannianas; Inchamentos de superfícies; CIÊNCIAS EXATAS E DA TERRA: MATEMÁTICA